THE AGE OF MARRIAGE ON INTERDISIPLINARY ISLAMIC LAW PERSPECTIVES - Iwan Romadhan Sitorus; Yusmita Yusmita (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2020)
Law Number 16 Year 2019 in article 7 provides an age limit for each person who will marry at the age of 19 years for men- and 19 years for women. The age limit given by the law does not look comprehensively in biological, sociological readiness, and so on. The modified law should be able to realize the benefit of the husband and wife in fostering the household. Determination of marriage age aims to protect offspring, create a family that is sawah mawaddah wa rahmah, maintain lineage, maintain family relationships, maintain diversity in the family, and prepare for maturity in the economy by paying attention to various aspects, both aspects, psychological, sociological, biological and certainly religious aspects. so that it can create a family in accordance with the marriage ceremony